2019
DOI: 10.3390/ijerph16071287
|View full text |Cite
|
Sign up to set email alerts
|

What Works? Prevention and Control of Sexually Transmitted Infections and Blood-Borne Viruses in Migrants from Sub-Saharan Africa, Northeast Asia and Southeast Asia Living in High-Income Countries: A Systematic Review

Abstract: Migration is a significant risk factor for the acquisition of human immunodeficiency virus (HIV), hepatitis B virus (HBV) and other sexually transmitted infections (STIs). An increasing proportion of these infections in high-income countries, such as Australia, are among migrants moving from low and middle-income countries with a high prevalence of HIV, HBV and other STIs. This systematic review explored the prevention and control of HIV, HBV and other STIs in migrants (>18 years) from Southeast Asia, North… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 74 publications
(234 reference statements)
0
21
0
Order By: Relevance
“…We recommend the use of conceptual and methodological frameworks such as transnationalism, intersectionality, SEM, and social determinants of health to better explore the intersection between gender, migration, and sexual and reproductive health inequalities. As with previous research [ 26 ], effective sexual health interventions for migrant populations are limited in HICs, an important consideration for those working within health promotion, education, and service delivery. Participatory approaches that build on community strengths are recommended [ 75 , 76 ].…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…We recommend the use of conceptual and methodological frameworks such as transnationalism, intersectionality, SEM, and social determinants of health to better explore the intersection between gender, migration, and sexual and reproductive health inequalities. As with previous research [ 26 ], effective sexual health interventions for migrant populations are limited in HICs, an important consideration for those working within health promotion, education, and service delivery. Participatory approaches that build on community strengths are recommended [ 75 , 76 ].…”
Section: Discussionmentioning
confidence: 76%
“…Whilst many studies recommended sexual health education for migrant women, the SEM suggests interventions focusing on individual health behaviour (such as education) may not be effective on their own given considerable influences on knowledge, attitudes, and behaviour experienced at the interpersonal and societal level. Previous research has demonstrated an absence of reported societal interventions to address STIs amongst migrants [ 26 ]. Women’s health, including their ability to develop sexual health literacy and navigate condom use, is strongly affected by sociocultural factors including social justice, gender equality, and human rights [ 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In effect, these people were allowed to continue engaging in risky sexual behavior. iii) Outreach testing depending on the situation (e.g., peculiar situations need analyses for migrants crossing borders) [118].…”
Section: Challenges For Societies In the Futurementioning
confidence: 99%
“…Increased migration has contributed to the spread of HIV, Hepatitis B Virus (HBV), and other STIs, with the vast majority of cases occurring in migrants from low-and middle-income countries who have moved to high-income countries. Most interventions in the United States of America, Australia, and Europe focus on individual behaviour rather than on broader sociocultural factors [5].…”
Section: Introductionmentioning
confidence: 99%